FIKIH WAQI’ - Ihsan Satrya Azhar (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This article aims at describing a Fiqh Waqi’, another essential tool in ijtihad or fatwa beside fiqh nushush or depth understanding of Alquran and hadist text, that mujtahid or mufti should use it in forming opinion or fatwa. Fiqh Waqi’ is depth understanding of the reality and actuality of the case. Actually it has been used in early islam but it doesn’t have a proper name in Ushul Fqih study. Fiqh Waqi’ is very important in contemporary world as the situation is changing from time to time. It assures accuracy of the opinion of Mujtahid or fatwa of Mufti.Key Words: waqi’, fiqh, realitas.